Impulsivity, Craving and Risky-Sexual-Behaviour in Brazilian Substance-Users: An Analytical Cross-Sectional Study - Sarah Naomi Foster; Pegoraro Natália Priolli Jora; Wagstaff Christopher; Adjei Richmond; Sekandi Patrick; Pillon Sandra Cristina (Journal of Psychosexual Health)
This study aimed to investigate the association between impulsivity, craving and risky sexual behaviour in Brazilian substance users. Substance-use disorder, according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), now features ‘craving’ as an essential criterion. Moreover, the intensity of craving and emotional dysregulation are factors considered pivotal to addressing risky sexual behaviour. Similarly, adverse childhood experiences, trauma, impulsivity and mental health conditions are considered to correlate to risky sexual behaviour. Research to date has focused on adolescent or student populations. A cross-sectional study design was utilised. The 135 participants were receiving treatment for substance-use disorder; the instruments used included the Barratt Impulsiveness Scale-11 (BIS-11), Sexual and Risk behaviour scale and the Behaviour Scale Crack Craving Questionnaire (CCQ-B) scale. Data was inputted into SPSS and analysed using the Pearson chi-squared test. The results included statistically significant correlations between craving and risky sexual behaviour, exposure to violence and risky sexual behaviour and perceptions of sexual addiction/ compulsion as being more of a problem than substance use. No statistical significance was found between socio-economic demographic data and risky sexual behaviour, or the primary substance and risky-sexual-behaviour. The limitations of the study were the small sample size, only male participants and language barriers. Implications for practice centre around synergising mental and physical health promotion via more proactive educational campaigns and accessible, equitable interventions. The study investigated the association between impulsivity, craving and risky sexual behaviour in Brazilian substance users receiving treatment. There were statistically significant correlations between craving and risky-sexual-behaviour, exposure to violence and risky sexual behaviour and a perception that sexual addiction/ compulsion is more of a problem than substance use.